Slow H2S-Releasing Donors and 3D Printable Arrays Cellular Models in Osteo-Differentiation of Mesenchymal Stem Cells for Personalized Therapies - Ilaria Arciero; Silvia Buonvino; Sonia Melino (Biomolecules)
The effects of the hydrogen sulfide (H2S) slow-releasing donor, named GSGa, a glutathione-conjugate water-soluble garlic extract, on human mesenchymal stem cells (hMSCs) in both bidimensional (2D) and three-dimensional (3D) cultures were investigated, demonstrating increased expression of the antioxidant enzyme HO-1 and decreased expression of the pro-inflammatory cytokine interleukin-6 (IL-6). The administration of the H2S donor can therefore increase the expression of antioxidant enzymes, which may have potential therapeutic applications in osteoarthritis (OA). Moreover, GSGa was able to promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), but not of cardiac mesenchymal stem cells (cMSCs) in a 2D culture system. This result highlights the varying sensitivity of hMSCs to the H2S donor GSGa, suggesting that the induction of osteogenic differentiation in stem cells by chemical factors is dependent on the tissue of origin. Additionally, a 3D-printable mesenchymal stem cells–bone matrix array (MSCBM), designed to closely mimic the stiffness of bone tissue, was developed to serve as a versatile tool for evaluating the effects of drugs and stem cells on bone repair in chronic diseases, such as OA. We demonstrated that the osteogenic differentiation process in cMSCs can be induced just by simulating bone stiffness in a 3D system. The expression of osteocalcin, RUNX2, and antioxidant enzymes was also assessed after treating MSCs with GSGa and/or increasing the stiffness of the culture environment. The printability of the array may enable better customization of the cavities, enabling an accurate replication of real bone defects. This could optimize the BM array to mimic bone defects not only in terms of stiffness, but also in terms of shape. This culture system may enable a rapid screening of antioxidant and anti-inflammatory compounds, facilitating a more personalized approach to regenerative therapy.